Synergistic effects of Persicaria odorata (Daun Kesom) leaf extracts with standard antibiotics on pathogenic bacteria - Ridzuan, P. M.; Hamzah, Hairul Aini; Shah, Anis; Mohd Hassan, Norazian; Baharudin, Roesnita (International Islamic University Malaysia Press, 2017)
Antibacterial activity of different types of P. odorata leaf extracts was evaluated in combination with standard antibiotics. Persicaria. odorata leaves were extracted with n-hexane (n-hex), dichloromethane (DCM) and methanol (MeOH). Each extract was applied on vancomycin (30μg), erythromycin (15μg) and gentamicin (10μg) discs, respectively. Disk diffusion method was used to evaluate the synergistic activity of each combination on Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes, Streptococcus pneumoniae, Pseudomonas aeruginosa, Salmonella typhi, and Escherichia coli. Minimum inhibitory concentration (MIC) and gas chromatography mass spectrometry (GCMS) analysis was performed on the active extract. Synergistic effects seen were mainly from the n-hex+antibiotics combinations, mainly on the Gram-positive bacteria (7 additive, 5 antagonistic), with MIC range from 50 μg/ml to 100 μg/ml, as well as Gram-negative bacteria (2 additive, 2 indifferent, 5 antagonistic). In particular, synergism showed by the combination of n-hex+van were all additive against the susceptible bacteria. DCM extract combination showed synergistic effects on three Gram-positive species (S. aureus, S. epidermidis, S. pyogenes). Meanwhile, MeOH+antibiotics combination showed significant additive synergistic effects (p<0.05) on S. aureus and S. epidermidis. The major compounds of leaves extract were decanal and β-citral. n-Hex extract superiorly inhibited Gram-positive bacteria growth as compared to DCM and MeOH extracts. The additive synergistic property of the n-hex P. odorata extract could be further studied for possible use as an antibacterial agent.